ekonomi syariah Peran Komunikasi Internal Untuk Meningkatkan Budaya Kerja Yang Positif di BMT Ngabar Ponorogo - Suyadi Suyadi; Joko Priono; Anisah Firdaus; Luhur Prasetyo (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
The Purpose of Writing This Article Discusses the Role of Internal Communication in Maintaining Good Relationships Between Employees and Leaders in Order to Improve a Positive Work Culture at BMT Ngabar Ponorogo. Internal communication aims to maintain good relationships between employees and management, avoid misunderstandings between employees and leaders, and also serve as a means of communication to convey aspirations and ideas within the BMT Ngabar Ponorogo environment. This research method utilizes a qualitative descriptive approach with primary data collection through direct interviews and observations, as well as secondary data from books, articles, websites, and blogs. The results of this study indicate that internal communication plays a crucial role in enhancing a positive work culture at BMT Ngabar.